The Benson Relaxation Technique in Reducing Anxiety Levels in Pre-Operative Cataract Patients - Putri Purnama Sari; Jenny Marlindawani Purba; Nunung Febrianty Sitepu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of the Benson relaxation technique on reducing anxiety levels in pre-cataract surgery patients. The research method uses a quasi-experimental research design. The Wilcoxon test results showed a significant difference in the mean anxiety score between the pretest and posttest in the control group (z=-5.247, p=0.000). In contrast, the Wilcoxon results showed that there was a significant difference in the level of anxiety—mean anxiety value between pretest and posttest in the intervention group (z=-5.518, p=0.000). Mann Whitney U test results showed z=-2.574, p=0.01). In conclusion, there is a significant influence on anxiety scores between the control group and the intervention group. Keywords: Cataract, Preoperative Anxiety, Benson Relaxation